Environmental, health, and business opportunities in the new meat alternatives market - Bogueva, Diana, 1974- (Business Science Reference, 2019)
"This book explores the new meat of the future, which is plant-based and covers alternatives to livestock and other animal products together with strategies to encourage their acceptability, marketing and business strategies. It also proposes ways for solving the global future food demand"--